Laryngeal osteosarcoma: Case report and literature review. Issue 2 (24th July 2014) - Kuba, Kiyomi; Inoue, Hitoshi; Hayashi, Takahiro; Matsumura, Satoko; Minami, Kazuhiko; Takajo, Humihiko; Morita, Kei; Nakahira, Mitsuhiko; Sugasawa, Masashi; Chen, Amy
ABSTRACT Background Sarcomas of the larynx are uncommon tumors, and osteosarcoma is the rarest. Only 24 cases of osteosarcoma of the larynx have been reported. The only case reported in Asia was from Thailand in 1981. Methods A 55‐year‐old male patient was referred to our hospital because of an 8‐month history of odynophagia and a gradually enlarging left neck mass. A neck CT scan was performed. A literature review was also performed for this report. Results The CT scan revealed extensive calcification with enlargement of the thyroid cartilage. The patient was diagnosed with osteosarcoma and was successfully treated by surgery alone. Conclusion Adequate surgical resection is required for successful treatment of laryngeal sarcomas. Adjuvant therapy is not contraindicated, but chemotherapy may improve the prognosis in patients with high‐grade tumors or metastatic disease. © 2014 Wiley Periodicals, Inc. Head Neck37: E26‐E29, 2015